2015
DOI: 10.1186/s13071-015-0968-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mosquito larval productivity among different land use types for targeted malaria vector control in the western Kenya highlands

Abstract: BackgroundMosquito larval source management (LSM) is likely to be more effective when adequate information such as dominant species, seasonal abundance, type of productive habitat, and land use type are available for targeted sites. LSM has been an effective strategy for reducing malaria morbidity in both urban and rural areas in Africa where sufficient proportions of larval habitats can be targeted. In this study, we conducted longitudinal larval source surveillance in the western Kenya highlands, generating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 56 publications
3
30
1
Order By: Relevance
“…A recent study reported a higher proportion of An. arabiensis (38.2%) in larval population [ 44 ]. The continued proportional increase in An.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported a higher proportion of An. arabiensis (38.2%) in larval population [ 44 ]. The continued proportional increase in An.…”
Section: Discussionmentioning
confidence: 99%
“…During the rainy season, the average proportion of positive mosquito breeding sites was found to be over 81% in both study areas. This results in differences in mosquito densities between dry and rainy seasons, which could be attributed to the availability of water and fluctuations in temperature and relative humidity [ 3 , 6 , 14 , 15 , 22 , 23 ]. In Sudan, adult mosquito density, i.e., An.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have shown that seasonality has an effect on An. gambiae sensu lato dynamics and abundance [ 15 , 16 ], and could demonstrate that anopheline mosquitoes are more sensitive to climatic variables, mainly temperature and relative humidity [ 21 , 27 , 32 ]. In this study, peak vector densities were observed during the rainy season and this result agrees with other observations from the same and other dry savanna areas of eastern and central Sudan [ 10 , 12 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the study, 300 anopheline larval habitats were identified in the three selected villages and characterized based on previous classification (Kweka, Munga, Himeidan, Githeko, & Yan, 2015; Kweka, Zhou, Lee, et al., 2011). In brief, larvae habitats were classified by habitat type (drainage ditches, abandoned gold mines, ponds, fish ponds, roadside canals, rock pools, and swamps) and then identified using unique numbers.…”
Section: Methodsmentioning
confidence: 99%